Design and Construction of An Integrated Smart Surveillance Network Using Perimeter Intrution Dictation (PID) and AI Cameras - Chidi, Amadi Christopher; Kelechi, Opara Felix; Chukwuchekwa, Nkwachukwu; Chika, Anyalewechi; Ifeanyi, Nnamdi Henry (Indo Green Journal, 2025)
This paper discusses the design and construction of a smart surveillance network that integrates perimeter intrusion detection (PID) with AI cameras. The setup includes a motion detection system, an authentication platform, an alert system, and a web application control panel. At the heart of this design is a Raspberry Pi, programmed with Python, which works alongside a PIR sensor and a camera for detecting motion and capturing images. Additionally, there's an RFID reader/card for authentication, a USB modem for making phone calls, and connecting the device to the internet, allowing it to send images of any intruder directly to the owner's email. An alarm buzzer is also part of the system, and the web application control panel can be accessed via the Raspberry Pi’s Wi-Fi for easy management. The system was tested under various scenarios, including user authentication and intruder detection, and it performed as expected.